From crowdfunding to digital banking: The evolution of funding societies - TAN, Swee Liang (Institutional Knowledge at Singapore Management University, 2020)
Kelvin Teo, Group CEO of peer-to-peer (P2P) lending platform Funding Societies Pte Ltd, has submitted an application for a Singapore digital wholesale bank (DWB) licence to the Monetary Authority of Singapore (MAS), Singapore’s central bank and financial regulator. For the purpose of this application, Funding Societies had set up a consortium with smartphone manufacturer Xiaomi Corp, investment bank AMTD Group, and electricity and gas grid operator SP Group. The questions that the case tackles include: Should Funding Societies remain a P2P lending platform or seek to become a digital bank? What were its reasons for choosing to team up with this specific set of consortium partners? Why did Funding Societies abandon its initial plan to be lead partner of the consortium? If the application failed, what should be its back-up plan? This case may be used for economics and finance courses at the undergraduate or postgraduate level. It teaches students to understand the contrast between theory and practice. Additionally, discussion of the case will enable students to gain an understanding of how P2P lending platforms are disrupting incumbent banks by acting as financial intermediaries. They would also appreciate the role of crowdfunding in promoting economic development by mitigating information asymmetry problems.